Gender perceptions of active mobility: Insights from three European cities - Carboni, A. (2021)
European cities have seen an increase in the use of personal means as an effect of the COVID-19 pandemic: they are asked to accelerate the shift towards more sustainable modes, as the active ones. The current paper tries to shed light on how the perception towards these latter modes changes according to gender. In the framework of H2020 TInnGO project, data collected through a survey in three European cities (Turin, Valencia, Paris) are investigated. Results show that women are more worried about safety, both while walking or riding a bike, as female cyclists do not appreciate sharing space with motor vehicles. Moreover, the absence of a dedicated space for children prevents women from starting to use bike-sharing. Comparing the results in the three cities provides interesting indications and suggestions for including the need of all active modes users in transport planning.